1994
DOI: 10.1017/s0266467400008087
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of two sympatric isopod species in a pine forest in central Java, Indonesia

Abstract: The populations of two dominant isopod species in a Pinus merkusii forest on the southern slope of mount Ungaran in central Java, Indonesia, were periodically sampled during one year using Tullgren extractions from soil cores. The aim of the research was to collect more information about the life-cycles of tropical isopods by analysing size-class distributions of two sympatric isopod species, belonging to the genus Burmoniscus. Biomass of the populations was estimated from length-weight conversions established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The soil type has been classified as brown andosol. A more detailed description can be found elsewhere (Vink and Purwanti, 1994; Krave et al. , 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The soil type has been classified as brown andosol. A more detailed description can be found elsewhere (Vink and Purwanti, 1994; Krave et al. , 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Pinus leaf litter has many components impalatable to edaphic animals (vink & purWanti, 1994), which raises the need for increasing litter palatability and digestibility by weakening its physical and chemical structure through microorganismal actions (haSSall & ruShton, 1984). In the Pinus case, fungi can be ingested along with litter (Soma & Saitô, 1983;haSSall & ruShton, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Some of them can survive high levels of metal in their food by modifying metal uptake and excretory rates [24]. Response of Diplopoda to metal pollution differs among species, as some species can be more abundant in polluted areas than in unpolluted sites [17,25]. Nevertheless, a recent study in comparable sites [6] showed the absence of correlation between Diplopoda density and soil metal content.…”
Section: Discussionmentioning
confidence: 99%